PEMBERDAYAAN AGAMA MASYARAKAT MELALUI GERAKAN “MAGHRIB MATIKAN TV AYO MENGAJI” DI KABUPATEN DEMAK - Rochanah, Rochanah (Community Development: Jurnal Pengembangan Masyarakat Islam, 2019)
AbstractThe Maghrib movement to turn off TV Ayo Mengaji aims to bring Demak Muslims back to further deepen their faith by studying the contents of the Koran. The reason behind the birth of the movement was due to the degradation of faith in the Muslim community Demak. Through the Gerakan, it is hoped that it will further add to the faith of the Muslim community in Demak in order to produce a young generation with moral character. The problem that the researchers raised in this study was; 1) How does the implementation of the Maghrib Movement Turn Off TV Come on to Study in Demak Regency? 2) What is the response of the Demak community in the implementation of the Maghrib Turn Off TV movement? This research is qualitative research with descriptive-analytical method. The technique of collecting data through observation, interviews and documentation. The results of the study show that; 1) the implementation of the TV turn off Maghrib movement namely; a) turn off the TV before the Maghrib prayer call is echoed, the community goes to a place of worship that is in their neighborhood to fulfill the Maghrib prayer congregation and afterwards recite the Qur'an. However, the movement in reality is still difficult to realize, meaning that it still cannot be implemented properly. The Demak Muslim community responded well to the movement, but it was still limited to verbal support, while the realization was not yet fully implemented.Keywords:       Religious empowerment, Maghrib turn off TV Ayo Mengaji, Demak community